The actual star [large type] : a novel - Byrne, Monica, 1981- (Harper Large Print, an imprint of HarperCollinsPublishers, 2021)
It takes readers on a journey over two millennia and six continents, telling three powerful tales a thousand years apart, all of them converging in the same cave in the Belizean jungle. Braided together are the stories of a pair of teenage twins who ascend the throne of a Maya kingdom; a young American woman on a trip of self-discovery in Belize; and two dangerous charismatics vying for the leadership of a new religion and racing toward a confrontation that will determine the fate of the few humans left on Earth after massive climate change. In each era, a reincarnated trinity of souls navigates the entanglements of tradition and progress, sister and stranger, and love and hate, until all of their age-old questions about the nature of existence converge deep underground, where only in complete darkness can they truly see.